The Caves of Wadi Al-Habis archaeological: A History engraved in the town of Ferzol-Beqaa in the Roman era - Fadlallah, Jaafar Zouheir (Journal of Humanities & Social Sciences, 2020)
Alike other towns in Beqaa governorate, the town of Ferzol involves in its past history, a revered heritage carved in rocks, places of worship and agriculture.The town of Ferzol is located in Zahle district – 6 km from Zahle and 58 km from the capital Beirut – at an altitude of around 1000 m above sea level. The number of its registered population is 1900.It is bordered from the east by the town of Ablah and from the northeast Nabi Ayla; from the north Qaa Er Rim town, Afrin and Mountain Sannine; from the west, it neighbors Al Karak and from the south the towns of Terbol and Dalhamiye.It was inhabited first by the tribe of Bani Assaf; the latter came from Syria and lived in Anjar and then moved on to Nabaa Al Habis in Ferzol and that was in the era of Bani Umayyah. But the region was famous before that as an episcopal center in the fifth century AD and as an ancient Christian center in Lebanon. Perhaps that reasoned ruined Zahle at one time before and for that the episcope moved into it only then to return to headquarters since the early eighteenth century AD. Yet its history certainly goes back to the Roman era due to the existence of a temple in respect to that period.The town has many tourist attractions, particularly archaeological grottos hewn in rocks, known as the Grottos of Habis, and is located in towering rocky cliffs. Both nature and the human hand have contributed in giving this current carved form.
Keywords: Farzel; Mughr al-Habis; Wadi al-Habis; Roman temple; King's Chair